Analisis Penerimaan Karyawan Terhadap Implementasi Sistem ERP dengan Metode TAM di Rumah Sakit X Gresik - Rahmawati, Nahardian Vica; Widhiani, Elsa Fatika; Kusdiyana, Ari; Nurdiana, Fara (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2025)
X Hospital in Gresik frequently encounters delays in financial reporting, prompting them to seek a solution by implementing an ERP system. This study aimed to examine the relationship between perceived ease of use and perceived usefulness with the level of acceptance at X Hospital in Gresik. The research design was quantitative, utilizing a cross-sectional method. The study employed a total sampling technique, involving 100 respondents. The findings indicated that 48 respondents (48%) rated X1 as good, 66 respondents (66%) rated X2 positively, and 49 respondents (49%) considered Y to be good. The results showed a significant relationship between perceived ease of use and acceptance levels, with a p-value of 0.000. Additionally, a significant relationship was found between perceived usefulness and acceptance levels, with a p-value of 0.002 at X Hospital. Regular monitoring and evaluation are necessary, considering the continuous technological updates received by users. The hospital is advised to conduct regular monitoring and evaluation to gather user feedback for ERP development.